Becoming User: Oracle, Barbara Gordon, and Representations of the User in Popular Culture - Dinnen, Zara (Camera obscura (Durham, NC), 2023)
This essay considers the figure of the “user” as an emergent subject of late twentieth‐century US culture, in relation to the World Wide Web and the 1990 Americans with Disabilities Act. The user is a subject position that is historical in the sense that use relations have always determined social formations within capitalism, but it has been newly energized in contemporary modes of capitalism after digital computing, and newly weighted in contemporary renderings of the nation‐state as service provider. This essay turns to a cultural moment in which a privatized user subject was coming into formation, using comic books of this moment to find the user figure and its stories. The DC Comics archive might not seem the most likely place to find answers to these concerns. But superhero origin stories are always about becoming user in late capitalist imaginaries. Superheroes learn to use their histories to reproduce the world they want. The then newly inaugurated DC Comics character Oracle, aka Barbara Gordon (formerly Batgirl), is becoming a wheelchair user and a computer user. Reading Oracle's 1990s user origin stories, this essay attends to scenes of wheelchair and computer use to work out a theory of user history and user time emerging in 1990s US culture. The comics reveal that the process of becoming user is always intersecting with the processes of becoming a racialized, gendered, classed, (dis)abled subject. They also open up the possibility for other affordances: becoming user as a process which can be torqued in its unfolding.